Penegakan Hukum Dan Pengawasan Terhadap Kewajiban Korporasi Reklamasi Pasca Tambang: PENEGAKAN HUKUM DAN PENGAWASAN TERHADAP KEWAJIBAN KOORPORASI REKLAMASI PASCA TAMBANG - Elviandri (UIR Press, 2022)
This study aims to analyze law enforcement and supervision of corporate post-mining reclamation obligations as well as to find an effective model of law enforcement and supervision of corporations in post-mining reclamation implementation. The research method used is normative juridical research. The results of the study show that law enforcement for corporations that do not carry out post-mining reclamation starting from Administrative Law, Civil Law and Criminal Law as a form of legal consequences for not carrying out an obligation is a repressive effort on a problem, because sanctions are one of the legal consequences that coercive when an obligation that has been mandated by a regulation is not carried out. In relation to the implementation of post-mining land reclamation activities as part of the process of utilizing natural resources, the sanction that can be applied is the obligation to pay fines to community mining business actors if the post-mining land reclamation activities are not carried out as planned. Giving the obligation to pay fines to these business actors does not eliminate the obligation of smallholder mining businesses and local governments to restore post-mining environmental damage by providing the lack of funds needed by third parties. This aims to provide a deterrent effect to other smallholder mining business actors . Keywords: Reclamation, Monitoring, Environment.